ENERGY ANALYSIS OF HYDROGEN USE IN ROAD TRANSPORT OF THE REPUBLIC OF CROATIA - Krog, Franco; Avsec, Jurij (Journal of Energy Technology, 2023)
In this paper, we will calculate the needs for hydrogen if all traffic in Croatia was driven by hydrogen. In the article, we will determine the required amount in several ways. First, we will briefly describe fuel cell cars and the extent to which the amount of exhaust gases would be reduced. We will then explain the ways of obtaining hydrogen, its transport and what the purchase costs would be. Finally, we will compare the results and draw some conclusions.